A Relation Between Moore-Penrose Inverses of Hermitian Matrices and Its Application in Electrical Networks - Yang, Yujun; Wang, Dayong; Klein, Douglas J. (Frontiers in Physics, 2020)
A novel relation between the Moore-Penrose inverses of two nullity-1 n × n Hermitian matrices which share a common null eigenvector is established, and its application in electrical networks is illustrated by applying the result to Laplacian matrices of graphs.